2000
DOI: 10.1063/1.126967
|View full text |Cite
|
Sign up to set email alerts
|

High-efficiency organic dye-doped polymer optical fiber lasers

Abstract: A graded-index polymer optical fiber containing rhodamine 6G in poly(methyl methacrylate-co-2-hydroxyethyl methacrylate) has been fabricated. Lasing behavior of the fiber was observed by pumping with a frequency-doubled Q-switched Nd: yttrium–aluminum–garnet laser. A slope efficiency of 43% and a lifetime of 110 000 shots at a repetition rate of 10 Hz have been observed. With a 1.5 mJ pump energy, an output energy of 640 μJ was produced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 14 publications
1
38
2
Order By: Relevance
“…Although it is beyond the scope of this paper to review polymer optical fiber laser and amplifiers research in this field has also expanded to this type of devices, resulting in a considerable number of reports on the operation of such sources [140][141][142][143][144][145][146][147].…”
Section: Dye-doped Polymer Amplifiersmentioning
confidence: 99%
“…Although it is beyond the scope of this paper to review polymer optical fiber laser and amplifiers research in this field has also expanded to this type of devices, resulting in a considerable number of reports on the operation of such sources [140][141][142][143][144][145][146][147].…”
Section: Dye-doped Polymer Amplifiersmentioning
confidence: 99%
“…[10][11][12][13][14][15] The range of tun· ability of laser dyes such as Rhodamine B and Ri» damine 6G usually lies between 570 and 640 nm. Tbe advantage of incorporating laser dyes in solid matrices such as POF is that it is easier and safer to handle them than when they are in liquid form.…”
Section: Introductionmentioning
confidence: 99%
“…Muto et al [18) investigated a dye doped step index polymer flber laser and Gvishi et al [19) reported lasing action in Rhodamine 6G (Rh 6G) doped solgel glass fiber. Also, Kuriki et al [20,21) reported lasing action of graded index POFs containing dyes such as Rhodamine B (Rh B), Rh 6G, and Perylene Orange. Also, photopumped narrow line laser emission is demonstrated using freestanding polymer films [22J, and cylindrical microcavities are formed by conjugated polymer thin films, dye doped polymers, and dendrimer doped polymers [23][24][25].…”
Section: Introductionmentioning
confidence: 99%